Performance and life cycle environmental benefits of recycling spent ion exchange brines by catalytic treatment of nitrate. (1st September 2015) - Choe, Jong Kwon; Bergquist, Allison M.; Jeong, Sangjo; Guest, Jeremy S.; Werth, Charles J.; Strathmann, Timothy J.
Abstract: Salt used to make brines for regeneration of ion exchange (IX) resins is the dominant economic and environmental liability of IX treatment systems for nitrate-contaminated drinking water sources. To reduce salt usage, the applicability and environmental benefits of using a catalytic reduction technology to treat nitrate in spent IX brines and enable their reuse for IX resin regeneration were evaluated. Hybrid IX/catalyst systems were designed and life cycle assessment of process consumables are used to set performance targets for the catalyst reactor. Nitrate reduction was measured in a typical spent brine (i.e., 5000 mg/L NO 3 − and 70, 000 mg/L NaCl) using bimetallic Pd–In hydrogenation catalysts with variable Pd (0.2–2.5 wt%) and In (0.0125–0.25 wt%) loadings on pelletized activated carbon support (Pd–In/C). The highest activity of 50 mg NO 3 − /(min − gPd ) was obtained with a 0.5 wt%Pd–0.1 wt%In/C catalyst. Catalyst longevity was demonstrated by observing no decrease in catalyst activity over more than 60 days in a packed-bed reactor. Based on catalyst activity measured in batch and packed-bed reactors, environmental impacts of hybrid IX/catalyst systems were evaluated for both sequencing-batch and continuous-flow packed-bed reactor designs and environmental impacts of the sequencing-batch hybrid system were found to be 38–81% of those of conventional IX. Major environmental impact contributors other than salt consumption include Pd metal, hydrogen (electron donor), and carbon dioxide (pH buffer). Sensitivity of environmental impacts of the sequencing-batch hybrid reactor system to sulfate and bicarbonate anions indicate the hybrid system is more sustainable than conventional IX when influent water contains <80 mg/L sulfate (at any bicarbonate level up to 100 mg/L) or <20 mg/L bicarbonate (at any sulfate level up to 100 mg/L) assuming 15 brine reuse cycles. The study showed that hybrid IX/catalyst reactor systems have potential to reduce resource consumption and improve environmental impacts associated with treating nitrate-contaminated water sources. Graphical abstract: Highlights: Hybrid IX/catalytic treatment technology for nitrate treatment evaluated. LCA combined with catalyst experimentation and IX model simulation. Pd–In/C catalysts treat nitrate-contaminated waste brines to allow reuse. Buildup of sulfate and bicarbonate in reused brines inhibits catalysts, but not IX. Hybrid system design of IX + sequencing batch catalyst reactor most sustainable.